The Figures and Meanings of Tengu: Semiotic Study of Mythological Creatures in Japanese Folklore - Ida Ayu Laksmita Sari (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
Japan is famous as an advanced manufacturing industrial country as a result of the high rationality in their works, however in daily life Japanese people still highly believe in the existence of Youkai, mythological creatures. This study examined the figures and meanings of Tengu, mythological creatures that are classified as Youkai which one of them is, as described in the Japanese folklore, having long nose and fully-red colored body. The data for this study are the folklore taken from the anthology book Nihon Mukashi Banashi 101 edited by Sayumi Kawauchi (2007). The figures and existence of Tengu in the folklore were practically analyzed using the Peirce's semiotic theory, with the focus on the meaning of icons, indexes, and symbols of Tengu in the folklore and the Japanese belief system. Moreover, this study revealed two figure types of Tengu namely daitengu, is a tengu whose long nose and kotengu whose eagle-like wings. In the Japanese belief system, it is believed that Tengu are mountain guardians, for example the Mount Takao, one of the places which is believed to be a Tengu habitat. Tengu is as well believed to have objects with supernatural powers such as kakuremino (a cloak) and ha uchiwa (a fan). The descriptions in the folklore clearly show that these Tengu actually exist, although the fact in reality is different. Regardless of either the presence or absence of these mythological creatures in the real world, furthermore, the folklore narrative shows that modern Japanese society still has a strong belief in the existence of Tengu. Stories about Tengu along with other mythological creatures continue to be passed on from a generation to another in both oral and written forms that indicates that Japanese people do not ever detach themselves from their old belief system.